The contrasting dynamics of the buoyancy-forced lofoten and greenland basins - Ypma, S.L. (author); Spall, M. A. (author); Lambert, E. (author); Georgiou, S. (author); Pietrzak, J.D. (author); Katsman, C.A. (author) (Journal of Physical Oceanography, 2020)
The Nordic seas are commonly described as a single basin to investigate their dynamics and sensitivity to environmental changes when using a theoretical framework. Here, we introduce a conceptual model for a two-basin marginal sea that better represents the Nordic seas geometry. In our conceptual model, the marginal sea is characterized by both a cyclonic boundary current and a front current as a result of different hydrographic properties east and west of the midocean ridge. The theory is compared to idealized model simulations and shows good agreement over a wide range of parameter settings, indicating that the physics in the two-basin marginal sea is well captured by the conceptual model. The balances between the atmospheric buoyancy forcing and the lateral eddy heat fluxes from the boundary current and the front current differ between the Lofoten and the Greenland Basins, since the Lofoten Basin is more strongly eddy dominated. Results show that this asymmetric sensitivity leads to opposing responses depending on the strength of the atmospheric buoyancy forcing. Additionally, the front current plays an essential role for the heat and volume budget of the two basins, by providing an additional pathway for heat toward the interior of both basins via lateral eddy heat fluxes. The variability of the temperature difference between east and west influences the strength of the different flow branches through the marginal sea and provides a dynamical explanation for the observed correlation between the front current and the slope current of the Norwegian Atlantic Current in the Nordic seas. Environmental Fluid Mechanics